BOOK REVIEW: ‟Editorial notes”, IUIES Journal, vol. 4, no. 1, 2017 (edited by the International University Institute of European Studies), Gorizia, 144 pp. - TUDOR, Salanțiu (Studia Universitatis Babes-Bolyai Studia Europaea, 2017)
IUIES Journal is a four monthly journal and which belongs to the International University Institute of European Studies. The first number from this year of the journal, propose as subject a surveillance of the First World War (FWW) with the occasion of the centenary starting from 2014 and in the next years since. In one way, the subject examined in this context wants to be a re-evoked of what this event means for the modern world and different dimensions that it captured.